2015
DOI: 10.1159/000437396
|View full text |Cite
|
Sign up to set email alerts
|

Bench Test for the Detection of Bacterial Contamination in Platelet Concentrates Using Rapid and Cultural Detection Methods with a Standardized Proficiency Panel

Abstract: Background: The most frequent infectious complication in transfusion therapy in developed countries is related to the bacterial contamination of platelet concentrates (PCs). Rapid and cultural screening methods for bacterial detection in platelets are available, but external performance evaluation, especially of rapid methods, has been difficult to realize so far. Here we summarize the results of three individual collaborative trials using an external quality assessment program (EQAP) for the application of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Apheresis‐derived single‐donor PCs were prepared as described previously . All donors provided informed consent that PCs may be used for research purposes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apheresis‐derived single‐donor PCs were prepared as described previously . All donors provided informed consent that PCs may be used for research purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Apheresis-derived single-donor PCs were prepared as described previously. 26 All donors provided informed consent that PCs may be used for research purposes. The final product consisted of 2.0 to 4.0 3 10E 1 11 platelets/U (205-295 mL) and 0.16 to 0.24 L/L ACD-A stabilizer and 0.76 to 0.84 L/L plasma/mL preparation.…”
Section: Bacterial Strains and Pc Collectionmentioning
confidence: 99%
“…The design of the proficiency panel samples described in this study demonstrated to be an effective tool to examine the performance of both, rapid and cultural detection methods in the same setting with ready‐to‐use sample material. The handling and applicability of sample material was further demonstrated by a pilot EQAP; in the meantime, additional EQAPs were conducted, also confirming these initial results . The innovative design of this EQAP concept permits the microbiological control of PCs under routine conditions, in contrast to other currently available EQAPs which fail to fulfil the real environmental conditions of bacterial screening with rapid detection methods.…”
Section: Discussionmentioning
confidence: 55%
“…Apheresis‐derived single‐donor PCs (APCs) and pooled PCs (PPCs) were prepared as described previously . All donors provided informed consent that platelets may be used for research purposes.…”
Section: Methodsmentioning
confidence: 99%
“…These include the BactiFlow flow cytometric assay or nucleic acid test. 25 BactiFlow has a limit of detection of 150 CFU/mL with ,1 hour result time. 26 Use of the BactiFlow detected 12 additional true positives (12/34 631; 1/2886) and 12 false positive (false positive rate of 0.03%).…”
Section: Other Testingmentioning
confidence: 99%